KONSEP DASAR UMPAN BALIK DALAM PEMBELAJARAN: SEBUAH KAJIAN PUSTAKA TENTANG PERAN DAN FUNGSINYA DALAM MENINGKATKAN HASIL BELAJAR - Tutin Darisa; Yuniarti Wahyuning Mastuti; Erniawati; Muhammad Misbakul Munir (STKIP Subang, 2026)
Feedback is an essential component of learning that plays an important role in improving the quality of the learning process and students’ learning outcomes. However, in practice, feedback is often limited to the provision of scores or brief comments and has not been optimally utilized as a tool for improving learning. This study aims to examine the basic concepts of feedback in learning and analyze its roles and functions in enhancing students’ learning outcomes. The study employed a qualitative approach using a library research method. Data were collected from various scientific literature sources, including academic books, national and international journal articles, and other relevant scholarly documents. Data analysis was conducted through content analysis and thematic analysis to identify key concepts, principles, and findings related to feedback in learning. The findings indicate that effective feedback should be specific, clear, relevant, and delivered in a timely manner. Feedback is also closely related to formative assessment because it helps students identify mistakes, strengthen conceptual understanding, increase learning motivation, and develop self-regulation and metacognitive skills. In addition, feedback functions as a pedagogical communication tool that supports more interactive and student-centered learning. Therefore, feedback can be concluded as a strategic element in learning that significantly contributes to improving the quality of both the learning process and learning outcomes when designed and implemented effectively.